Effect of propolis extract on guines pig lung mast cell - R. O. Orsi; J. M. Sforcin; S. R. C. Funari; J. C. Gomes (Journal of Venomous Animals and Toxins including Tropical Diseases, 2005)
The direct effect of ethanolic extract of propolis on guinea pig lung cell suspension containing mast cells, as well as its influence on the histamine release induced by antigen (ovoalbumin 10 mug/ml) and ionophore A 23187 (3 muM) were investigated. Propolis ethanolic extract (300 mug/ml) increased the histamine release in guinea pig lung suspension containing mast cells by a cytotoxic effect. Lower concentrations of propolis had no effect on histamine release. Our results demonstrated that propolis (3, 10, 30, and 100 mug/ml) shows no significant effect on the histamine release induced by ionophore and antigen. Based on these results, we suggest that propolis could directly activate mast cells, promoting inflammatory mediators release by cytotoxic mechanisms, what could be related to allergic processes in propolis sensitive people.